Broilers fed with diets of restricted consumption containing seje palm oil (Oenocarpus bataua) (Revista Sistemas de Producción Agroecológicos, 2015)
For the small-scale poultry industry be profitable, is necessary to find alternative feeding, using raw materials available in each region, so that palm of seje (Oenocarpus bataua) is a native resource, valuable and low use in the Orinoco region; its fruit oil of high nutritional quality is obtained, similar in content to the fatty acids of olive oil. This experiment was conducted in the Natural Reserve Las Unamas, located in the municipality of San Martin, Meta, seventy two broilers were used, in a completely randomized design with four treatments and three replicates of six chicks each one, to which are supplied with restricted diets with different levels of consumption of oil seje palm, the four treatments were evaluated: T1 = commercial concentrate (energy from carbohydrates), T2 = energy source palm oil (APA), T3 = 10% replacement of oil by APA seje (AS), T3 = replacement of 10% APA by oil seje (AS), and T4 = replacement of 20% APA by AS. The evaluated variables were the total weight gain (g): 1362, 1179, 1530.8 and 1678.6 for T1, T2, T3 and T4 respectively (P
Keywords: african palm; fatty acids; food; energy